(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article examines issues related to developing riskological competence among prospective teachers within contemporary educational paradigms. It highlights the importance of equipping future educators with skills necessary to identify, assess, and manage risks effectively in an increasingly complex and uncertain environment. The study discusses various strategies aimed at fostering this competency through targeted training programs, practical exercises, and collaborative learning experiences. Furthermore, it emphasizes the need for reforming teacher education systems to ensure that graduates are well-prepared to navigate modern challenges successfully.